Intestinal Microbiota Contributes to the Improvement of Alcoholic Hepatitis in Mice Treated With Schisandra chinensis Extract - Xiang, Jun-Yan; Chi, Yan-Yu; Han, Jin-Xin; Shi, Xinyu; Cai, Yong; Xiang, Hongyu; Xie, Qiuhong (Frontiers in Nutrition, 2022)
Alcoholic hepatitis (AH) has a high short-term mortality rate. Schisandra chinensis has the potential to ameliorate liver damage and be a source of prebiotics. We aimed to investigate whether Schisandra chinensis extract (SCE) can improve AH and the role of the small intestinal and cecal microbiota and their metabolites. UHPLC-QE-MS was used to analyze the chemical components of SCE. The chronic-plus-binge ethanol feeding model was used to induce AH in mice. 1H NMR was used to analyze intestinal metabolites. 16S rRNA-based high throughput sequencing was used to evaluated the effects of SCE on intestinal microbiota (IM). Intestinal microbiota transplantation was used to explore the role of IM in SCE treatment of AH. SCE ameliorated AH non-dose-dependently. SCE effectively improved liver inflammation and oxidative/nitrosative stress, strengthened intestinal barrier function, and regulated the composition of IM and the content of short-chain fatty acids (SCFAs) in AH mice. Samples from in vivo and in vitro SCE-altered IM improved liver status and regulated the IM. The administration of Lactobacillus plantarum and Bifidobacterium breve ameliorated AH to some extent. The administration of Enterococcus faecalis and Klebsiella oxytoca had partial beneficial effects on AH. Collectively, IM and metabolites were closely associated with the improvement of SCE on AH. The possible microbe targets were the growth inhibition of Escherichia-Shigella and the expansion of SCFA producers, such as Lactobacillus and Bifidobacterium. Schisandra chinensis can be considered as a safe and effective dietary supplement for the prevention and improvement of AH.